Performance evaluation of plagiarism detection method based on the intermediate language - Juričić, Vedran (Array, 2011)
This paper presents detection method for source code plagiarism that is based on the intermediate language, and shows its usage in e-learning. Method is tested on the appropriate number of test cases that represent the most frequent code modification techniques. Results and its performance are compared to the existing source code plagiarism detection methods implemented in some of the most known plagiarism detection systems and applications.